Meaningful, Enjoyable, and Conscious Learning: Perspectives of Elementary School Teachers and Students in Makassar and Pulau Sembilan - Nurwidyayanti; Andi Irwandi; Burhan; Achmad Fajar Muhammad (Universitas Pendidikan Ganesha, 2026)
Elementary school learning is still predominantly oriented toward academic achievement and content mastery, providing limited opportunities for students to experience meaningful, enjoyable, and conscious learning. This condition reflects a gap between the principles of deep learning, which emphasize cognitive, emotional, and reflective engagement, and classroom practices that remain largely teacher-centered and outcome-oriented. This study aims to analyze and explore the implementation of meaningful, enjoyable, and conscious learning from the perspectives of elementary school teachers and students as essential dimensions of deep learning. A qualitative phenomenological design was employed involving teachers and students from seven elementary schools. Data were collected through in-depth interviews, participant observation, and document analysis and analyzed using thematic analysis. The findings indicate that teachers implemented meaningful learning by connecting lessons with students’ real-life experiences, enjoyable learning through interactive and creative activities, and conscious learning through reflective practices that foster self-awareness and active participation. These integrated dimensions create a more engaging and holistic learning environment. This study concludes that meaningful, enjoyable, and conscious learning provides a strong pedagogical foundation for implementing deep learning and offers practical guidance for designing student-centered learning environments in elementary education.